STRATEGI KOMUNIKASI VOLUNTARY COUNSELING TEST (VCT) TERHADAP PENDERITA HIV/AIDS (ODHA) DI MALANG - Rizki Agung Novariyanto (IKIP Budi Utomo Malang, 2017)
HIV / AIDS is still one of the dreaded disease by a large part of society, because they still consider HIV / AIDS as a deadly disease , there is no cure and the disease is a curse . This is caused due to an incorrect myths about HIV / AIDS . Due to the myth , making people living with HIV / AIDS (PLWHA ) are stigmatized and discrimination . Stigma and discrimination are two things that are often experienced by people living with HIV . Because of the stigma and discrimination that people living with HIV be afraid , afraid to open up for fear of being shut excluded so that people living with HIV and people living with HIV closure that makes HIV / AIDS is difficult to detect its spread . To overcome these problems, one of which is through Voluntary Counseling Test ( VCT ) . VCT counseling is an activity that provides psychological support , information and knowledge of HIV / AIDS , prevent the transmission of HIV, promote responsible behavior change , treatment and ensure solving various problems associated with HIV / VCT AIDS.Ada in two stages , namely the stage of Pre- Test and Post- Tests . In the Pre- test counseling is done stage by providing information about HIV / AIDS , prevention , transmission and window period. Pre- test counseling provides knowledge about the benefits of HIV testing , testing for decision making, and planning for issues facing HIV . After HIV Testing and Counseling Pre PLWHA PLWHA undergo the HIV test will undergo stages of post counseling where PLHIV will be conditioned to accept the results of the HIV test , get information about what to do if the results of his HIV test is positive or negative , andmost importantly so that people living with HIV do not become stress , depression and despair. VCT is run by counselors who are trained and experienced in this study bidangnya.Pada researchers conducted a study using qualitative methods to the three counselors that have been set using purposive sampling method and data captured through interviews and counseling in VCT observasi.Ketika Pre Test and post- test , the counselor needs a communications strategy that will be used to affect people living with HIV in order to receive the message delivered by the counselor and the main thing is to change the behavior of people living with HIV. Based on the results of research conducted by the researchers of the communication strategy VCT Pre Test and Post- Test in Dr. Saiful Anwar Hospital Malang against people living with HIV , it was found that the result is a persuasive communication strategies used by counselors when doing koneling to PLWHA HIV Testing Pre and Communication , Information andEducation (CIE ) is a communication strategy that is used by counselors when counseling Post- test counseling is done by the counselor was tailored to what the existing problems in people living with HIV with the ultimate goal , namely a change in the behavior of people living with HIV.